Extração de potássio a partir da rocha Verdete empregando ácidos orgânicos e fungos - Duarte, Lorrane Marques (2019)
Brazil imports most of the potassium (K) that is applied as fertilizer in agriculture. This happens because Brazilian sources of high solubility K are still underexploited and those of low solubility, such as the Verdete rock, require the development of technologies that make it feasible to use in agriculture. Biosolubilization may be one of these technologies for producing potassic fertilizers from low-solubility rocks. Filamentous fungi produce, as part of their metabolic activity, organic acids capable of solubilizing minerals and make nutrients available. Organic acids solubilize minerals through acidolysis, caused by protons released from carboxyl groups, and by complexation of the metals present in the structure of the mineral. Thus, in this work the extraction of K from Verdete rock was evaluated by means of solubilization by organic acids or by microorganisms producing these acids. The experiments were carried out in 125 mL erlenmeyers with 40 mL of citric acid solution or oxalic acid at a concentration of 2% (w v) and 0.4 g of Verdete. The erlenmeyers were incubated under 100 rpm shaking and destructive samples were collected at 3, 6, 9, 12, 24, 48, 72, 96 and 120 h with 3 replicates. Another experiment was carried out with oxalic acid concentrations of 2, 4, 6, 8 and 10% incubated for 12, 24, 48 and 72 h with Verdete. Samples were filtered and analyzed for soluble K concentration by flame photometry. The solubilization of K by fungi was evaluated in 250 mL erlenmeyers containing 100 mL of the Aleksandrov medium, with the K source being replaced with 0.2% of Verdete. Filamentous fungi Penicillium pinophilum, Penicillium islandicum, Penicillium purpurogenum, Aspergillus niger and Eupenicillium ludwigii were tested. The erlenmeyers were incubated on an orbital shaker for 5 days under shaking at 150 rpm at 30 °C. Oxalic acid was more efficient in the solubilization of K compared to citric acid, releasing up to 6.5% of the K contained in Verdete, whereas citric acid released 2.3% of K. Solubilization with oxalic acid is dependent on the concentration of the acid and the reaction time, the latter being the factor with the greatest effect on the solubilization. X-ray diffraction analysis of the remaining solids and the material in solution after attack with oxalic acid indicated that K is solubilized from the mica component of Verdete, forming potassium oxalate (K2C2O4). The direct application of organic acid-producing fungi to Verdete solubilization was not efficient. The culture medium Aleksandrov limited fungal growth due to its low concentration of glucose and absence of a nitrogen source.